The effect of berberine supplementation on obesity indices: A dose– response meta-analysis and systematic review of randomized controlled trials. (May 2020) - Xiong, Pan; Niu, Li; Talaei, Sam; Kord-Varkaneh, Hamed; Clark, Cain C.T.; Găman, Mihnea-Alexandru; Rahmani, Jamal; Dorosti, Masoumeh; Mousavi, Seyed Mohammad; Zarezadeh, Meysam; Taghizade-Bilondi, Hossein; Zhang, Jitao
Abstract: Background: and purpose: Clinical studies investigating the effects of berberine supplementation on anthropometric indices in humans have generated inconsistent results. Thus, the objective of this systematic review and meta-analysis was to clarify the effects of berberine supplementation on obesity indices in human subjects. Methods: Several online medical databases were systematically searched up to February 2019. All clinical trials exploring the effects of berberine supplementation on indices of obesity were included. The combined weighted mean difference (WMD) of eligible studies was assessed using a random-effects model. We evaluated publication bias by using the Egger's test. Results: Overall, 10 studies were included. The combined outcomes suggested a significant influence of berberine administration on body mass index (BMI) (WMD: −0.29 kg/m 2, 95% CI: −0.51 to −0.08, p = 0.006) and waist circumference (WC) (WMD: −2.75 cm, 95% CI: −4.88 to −0.62, p = 0.01). However, berberine supplementation yielded no significant decline in body weight (BW) (WMD: −0.11 kg, 95% CI: −0.99 to 0.76, p = 0.79). Following the dose-response evaluation, berberine intake was found to significantly reduce BMI (r = −0.02) and WC (r = −0.72) based on treatment duration. Conclusion: The results of the current study support the use of berberine supplementation for the improvement of obesity indices. Highlights: Berberine supplementation significantly reduces body mass index (BMI). Berberine supplementation significantly reduces waist circumference (WC). Changes in BMI and WC manifested in a dose-response manner.